The fungal core effector Pep1 is conserved across smuts of dicots and monocots. Issue 3 (27th January 2015) - Hemetsberger, Christoph; Mueller, André N.; Matei, Alexandra; Herrberger, Christian; Hensel, Götz; Kumlehn, Jochen; Mishra, Bagdevi; Sharma, Rahul; Thines, Marco; Hückelhoven, Ralph; Doehlemann, Gunther
Summary: The secreted fungal effector Pep1 is essential for penetration of the host epidermis and establishment of biotrophy in the Ustilago maydis –maize pathosystem. Previously, Pep1 was found to be an inhibitor of apoplastic plant peroxidases, which suppresses the oxidative burst, a primary immune response of the host plant and enables fungal colonization. To investigate the conservation of Pep1 in other pathogens, genomes of related smut species were screened for pep1 orthologues. Pep1 proteins were produced in Escherichia coli for functional assays. The biological function of Pep1 was tested by heterologous expression in U. maydis and Hordeum vulgare . Pep1 orthologues revealed a remarkable degree of sequence conservation, indicating that this effector might play a fundamental role in virulence of biotrophic smut fungi. Pep1 function and its role in virulence are conserved in different pathogenic fungi, even across the monocot–dicot border of host plants. The findings described in this study classify Pep1 as a phylogenetically conserved fungal core effector. Furthermore, we documented the influence of Pep1 on the disease caused by Blumeria graminis f. sp. hordei which is a non‐smut‐related pathosystem.